1982
DOI: 10.1159/000156060
|View full text |Cite
|
Sign up to set email alerts
|

The Nocturnal Behavior of Caged Rhesus Monkeys (Macaca mulatta )

Abstract: The behavior of rhesus monkeys (Macaca mulatta) was observed via videotape recording during the 12 hour period from 6.00 p.m. to 6.00 a.m. Adult animals were housed in male/female pairs under one of three cage conditions: individual cage, mating cage and a larger ‘group’ cage. 20 categories of behavior were assessed and the resultant behavior was described and quantitatively compared across cage conditions. The animals spent almost the entire night in a sitting position, either alone or while huddling with ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Patients with insomnia report difficulty in maintaining sleep, i.e., having intermittent awakening the night (Li et al, 2002). In terms of their characteristic nocturnal inactivity, monkeys spontaneously awake frequently and they often scratch themselves or shift posture and then return to sleep (Erffmeyer, 1982). Although human female emotional characteristics are different from those of female monkeys, it is possible that the present finding of higher nocturnal locomotion in the females is associated with something of an emotional characteristic in the human female.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Patients with insomnia report difficulty in maintaining sleep, i.e., having intermittent awakening the night (Li et al, 2002). In terms of their characteristic nocturnal inactivity, monkeys spontaneously awake frequently and they often scratch themselves or shift posture and then return to sleep (Erffmeyer, 1982). Although human female emotional characteristics are different from those of female monkeys, it is possible that the present finding of higher nocturnal locomotion in the females is associated with something of an emotional characteristic in the human female.…”
Section: Discussionmentioning
confidence: 68%
“…These factors make nonhuman primates valuable animal models for studies of the functional effects of neurotoxicants. A previous behavioral study using videotape recording showed the behavior of the rhesus monkey in the home cage (Erffmeyer, 1982). They tend to be inactive during the dark period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of social interaction can make the decision of whether or not to leave two animals paired particularly difficult. Macaques that have an affiliative relationship might huddle together at night [Erffmeyer, 1982; Eaton et al, 1994], even if they have not been observed in relaxed close proximity during daytime observations. If a thorough assessment indicates the pair is not engaging in substantial positive interactions, finding different partners for each should be considered to increase welfare.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive analysis of the normal sleep of M. mulatta (rhesus) monkeys is a prerequisite if we are to understand the changes in sleep following experimental manipulations that may not be possible in humans and to extrapolate their relevance to the human condition. Direct observation in the field 4 and laboratory-based video observation 5 employing infrared technology have provided insight into the general nocturnal behavior in M. mulatta. These observations establish that this is a diurnal species, i.e., active during the day and inactive, presumably sleeping, at night.…”
Section: Introductionmentioning
confidence: 99%